1995
DOI: 10.1042/bj3070099
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the mitochondrial permeability transition to lethal injury after exposure of hepatocytes to t-butylhydroperoxide

Abstract: We have developed a novel method for monitoring the mitochondrial permeability transition in single intact hepatocytes during injury with t-butylhydroperoxide (t-BuOOH). Cultured hepatocytes were loaded with the fluorescence probes, calcein and tetramethylrhodamine methyl ester (TMRM). Depending on loading conditions, calcein labelled the cytosolic space exclusively and did not enter mitochondria or it stained both cytosol and mitochondria. TMRM labelled mitochondria as an indicator of mitochondrial polarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
267
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(272 citation statements)
references
References 35 publications
5
267
0
Order By: Relevance
“…copy to disting,.,:s~-, mitochondrial from cytosolic fluorescence, since the thickness of our confocal sections (0.8-0.9 pro) is only slightly less than the diameter of a cardiac myocyte mitochondrion. In hepatocytes, Nieminen and co-workers [32] developed an approach to load calcein, a fluorescent marker, almost exclusively into the cytosol. Confocal microscopy of such calcein-labeled hepatocytes showed mitochondria as dark voids in a background of diffuse bright cytosolic fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…copy to disting,.,:s~-, mitochondrial from cytosolic fluorescence, since the thickness of our confocal sections (0.8-0.9 pro) is only slightly less than the diameter of a cardiac myocyte mitochondrion. In hepatocytes, Nieminen and co-workers [32] developed an approach to load calcein, a fluorescent marker, almost exclusively into the cytosol. Confocal microscopy of such calcein-labeled hepatocytes showed mitochondria as dark voids in a background of diffuse bright cytosolic fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the MPT possesses at least two redox-sensitive sites, one of them in equilibrium with GSH of mitochondrial matrix and another that can be directly activated by ROS [30]. Therefore, in addition to the oxidation of membrane protein sulfhydryl groups, the oxidation of both GSH and NAD(P)H of mitochondrial matrix [30], followed closely by an increase in the mitochondrial Ca 2 + and ROS generation within mitochondria (or a decreasing in their detoxification), contributes to the MPT induction, as shown by studies with several MPT inducers, including tert-butylhydroperoxide [39][40][41][42] and inorganic phosphate [31,43]. Besides the generation of ROS, NO can also act on mitochondria amplifying the signals promoting the MPT [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cyclosporine A, a well-known PTP blocker [64][65][66] has no effect on MAC activity, which reinforces the notion that MAC and the PTP are independent. 29 It has been shown that trifluoperazine and propranolol prevent apoptosis in some cell lines, 67,68 and trifluoperazine and dibucaine also block mitochondrial depolarization induced by glutamate in neurons. 69 Dibucaine, trifluoperazine and propranolol also block cytochrome c release from mitochondria induced by recombinant Bax and 'BH3 domain-only' proteins like t-Bid.…”
Section: Pharmacology Of Mac/bax Channelsmentioning
confidence: 99%